BS EN ISO 389-3 AMD1. Acoustics. Reference zero for the calibration of audiometric equipment. Part 3. Reference equivalent threshold vibratory force levels for pure tones and bone vibrators (17th February 2020) - British Standards Institution,
No abstract available